KARAKTERISTIK PENDIDIKAN ANAK USIA DINI - Safitri Zubaidah; Lailatun Nasuhah (Al'Adalah, 2016)
Education is very important in human’s life. Every people are able to get it. It can be started from children to old people. As what wise word say that never say old to learn. It means that everyone can get an education whether they are children or old people. Toddler education has an important factor in establishing the country, since they are the next generation in the country. The country will grow up, develop, or collapse depends on them. Hence, toddler education must be prepared and planned well, so that the country has the next generation who has good faith, intelligent, skillful, and the most important thing is they must be useful to the family, religion, and country.